Panhypopituitarism presenting as sick sinus syndrome: a case series - Rajakumar, Priyadarshini; Anand Sheya,; Adlyne Reena Asirvatham,; Ranjan, Asha; Mahadevan, Shriraam (Journal of the Pakistan Medical Association, 2025)
The objective of this study is to report the cases of three patients who presented with sick sinus syndrome associated with secondary hypothyroidism, requiring permanent pacemaker insertion and hormone replacement therapy. Three patients were diagnosed with sick sinus syndrome and permanent pacemaker insertion was planned. All three were in their sixth and seventh decades, with clear features of long-standing neglected panhypopituitarism. They had inappropriately low thyroid stimulating hormone (TSH) elevation for the low free thyroid hormonal levels. But since their initial screening was with TSH alone, which was normal in two patients, the diagnosis of central hypothyroidism was missed. Despite all these, all three improved dramatically just with steroids and thyroxine supplements, proving the endocrinological drive in rhythmicity, despite other propositions. This article highlights the importance of multiple endocrinological drivers of sino-atrial nodal rhythmicity and how the possibility of pituitary insufficiency should be considered before going in for an invasive approach like pacemaker insertion. Keywords: Panhypopituitarism, Cardiac arrhythmia, Sick sinus syndrome.